Factors Influencing the Psychological Wellbeing of Adolescent Girls in Coastal Bangladesh: A Cross-Sectional Study (Journal of the Medical College for Women & Hospital, 2026)
Background: Psychological wellbeing during adolescence is influenced by socio-demographic, menstrual, and environmental factors. Adolescents in coastal regions of Bangladesh are frequently exposed to natural disasters, which may further affect their wellbeing. Aim: This study aimed to assess the factors influencing psychological wellbeing among adolescent girls in a coastal district of Bangladesh. Materials and Method: A descriptive cross-sectional study was conducted from January to December 2023 among 307 adolescent girls (classes 9–12) from three secondary schools and one college in Jhalokathi district, Bangladesh. Data were collected using a pre-tested semi-structured questionnaire, including socio-demographic information, menstrual history, and Ryff’s 42-item Psychological Well-Being Scale. Results: Most participants were aged 14–15 years (57.7%) and practiced Islam (85.3%). The majority had secondary education or below (82.1%) and lived in nuclear families (86.3%). Floods were the most commonly experienced disaster (85.3%), with most adolescents staying at home (87.0%). Mean psychological wellbeing scores were highest for self-acceptance (29.9±4.8) and lowest for purpose in life (25.8±5.4). Menstrual characteristics and symptoms were prevalent, with 73.0% reporting regular cycles and 79.2% experiencing abdominal pain. Regular menstrual cycles and absence of fatigue were significantly associated with higher autonomy (p=0.019, p=0.003). Younger age, staying at home during disasters, sanitary pad use, and certain menstrual symptoms were linked to higher environmental mastery and personal growth. Positive relations and self-acceptance were significantly influenced by menstrual regularity, menstrual flow, and family income (p